Adaptive Mechanisms of Mycobacterium tuberculosis: Role of fbiC Mutations in Dormancy and Survival - Parissa Farnia; Mohsen Maleknia; Poopak Farnia; Jalaledin Ghanavi (International Journal of Mycobacteriology)
This review examines the impact of F420 biosynthesis protein C (fbiC) mutations in Mycobacterium tuberculosis (Mtb) and their influence on the bacterium’s dormancy mechanisms. The potential role of fbiC mutations and functional impairments in the persistence of Mtb is emphasized. Tuberculosis (TB) bacilli can enter a dormant state with minimal metabolic activity, allowing them to conserve resources and survive in low-nutrient, low-oxygen environments for extended periods. While the fbiC gene contributes to dormancy, Mtb can achieve this state through multiple genetic and metabolic pathways, suggesting that it may still undergo dormancy even with functional impairments in fbiC. In this review, we utilized several scientific databases, including PubMed, Web of Science, and Google Scholar, and set of key search terms including “fbiC gene,” “F420 Biosynthesis,” “Mycobacterium tuberculosis,” “Dormancy,” and “Drug Resistance” to highlight the significance of the fbiC gene in regulating dormancy and explore how Mtb compensates for fbiC dysfunction through various metabolic adaptations.